Transcriptome-wide Identification and Expression Analysis of Brachypodium distachyon Transposons in Response to Viral Infection - Tuğba Gürkök (Turkish Journal of Agriculture: Food Science and Technology)
Transposable elements (TEs) are the most abundant group of genomic elements in plants that can be found in genic or intergenic regions of their host genomes. Several stimuli such as biotic or abiotic stress have roles in either activating their transcription or transposition. Here the effect of the Panicum mosaic virus (PMV) and its satellite virus (SPMV) infection on the transposon transcription of the Brachypodium distachyon model plant was investigated. To evaluate the transcription activity of TEs, transcriptomic data of mock and virus inoculated plants were compared. Our results indicate that major components of TEs are retroelements in all RNA-seq libraries. The number of transcribed TEs detected in mock inoculated plants is higher than virus inoculated plants. In comparison with mock inoculated plants 13% of the TEs showed at least two folds alteration upon PMV infection and 21% upon PMV+SPMV infection. Rather than inoculation with PMV alone inoculation with PMV+SPMV together also increased various TE encoding transcripts expressions. MuDR-N78C_OS encoding transcript was strongly up-regulated against both PMV and PMV+SPMV infection. The synergism generated by PMV and SPMV together enhanced TE transcripts expressions than PMV alone. It was observed that viral infection induced the transcriptional activity of several transposons. The results suggest that increased expressions of TEs might have a role in response to biotic stress in B. distachyon. Identification of TEs which are taking part in stress can serve useful information for functional genomics and designing novel breeding strategies in developing stress resistance crops.